(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
It is essential to take a separate approach to the organization of independent learning activities of students, where the individual approach is often carried out on a selective basis through the content of the proposed tasks. In this article, the author discusses how to increase the effectiveness of education through the independent learning of students in higher education today, the development of their cognitive abilities.